Prolonged Gut Dysbiosis and Fecal Excretion of Hepatitis A Virus in Patients Infected with Human Immunodeficiency Virus - Aya Ishizaka; Michiko Koga; Taketoshi Mizutani; Lay Ahyoung Lim; Eisuke Adachi; Kazuhiko Ikeuchi; Ryuta Ueda; Haruyo Aoyagi; Satoshi Tanaka; Hiroshi Kiyono; Tetsuro Matano; Hideki Aizaki; et al. (Viruses, 2021)
Hepatitis A virus (HAV) causes transient acute infection, and little is known of viral shedding via the duodenum and into the intestinal environment, including the gut microbiome, from the period of infection until after the recovery of symptoms. Therefore, in this study, we aimed to comprehensively observe the amount of virus excreted into the intestinal tract, the changes in the intestinal microbiome, and the level of inflammation during the healing process. We used blood and stool specimens from patients with human immunodeficiency virus who were infected with HAV during the HAV outbreak in Japan in 2018. Moreover, we observed changes in fecal HAV RNA and quantified the plasma cytokine level and gut microbiome by 16S rRNA analysis from clinical onset to at least 6 months after healing. HAV was detected from clinical onset up to a period of more than 150 days. Immediately after infection, many pro-inflammatory cytokines were elicited, and some cytokines showed different behaviors. The intestinal microbiome changed significantly after infection (dysbiosis), and the dysbiosis continued for a long time after healing. These observations suggest that the immunocompromised state is associated with prolonged viral shedding into the intestinal tract and delayed recovery of the intestinal environment.